Serologic and Molecular Detection of Mycoplasma gallisepticum in Layer Flocks in South Marmara Region of Turkey - Goncagül, Gülşen; Kardoğan, Özlem; Çokal, Yavuz; Günaydin, Elçi̇n (Sciencedomain International, 2021)
Background: Due to the economic impacts of Mycoplasma gallisepticum (MG) infection in poultry, it is essential to have a fast, reliable and accurate diagnostic test to diagnose the infection.
Aims: It was aimed to examine the presence of MG in the South Marmara Region of Turkey where extensive commercial layer flocks exist by RPA, ELISA and real-time PCR.
Materials and Methods: In the study, 981 sera and 160 tracheal swab samples (20 swabs per each flock) obtained from eight layer flocks were examined for the presence of MG-antibody by RPA, ELISA, and the presence of MG by real-time PCR, respectively.
Results: MG-seropositive flock rate was determined to be 100% by RPA. Twenty-three of the RPA positive sera in each flock LA, LB, LC, LD, LF, LG, and 17 RPA positive sera in flock LE (due to 17 positive RPA sera obtained) were examined for the presence of MG antibody by ELISA, and MG-seropositive flock rate was determined to be 87.5%. As a result of the examination of a total of 32 tracheal swab samples (20 swabs perflock/5 swabs=4 pooled samples, 8 flocksX4 pooled samples= 32 samples) for the presence of MG, real-time PCR positive flock rate was found to be 75%.
Conclusion: To decide the flock whether it is infected or not and the initiate effective preventive measures against MG infection as soon as possible; serology should be applied simultaneously with bacteriology and/or PCR to prevent time loss due to shortcomings of serological tests used as primary screening test such as cross reactions, sensitivity and specificity problems.
Keywords: 2. Zero hunger; 8. Economic growth; 3. Good health